PENENTUAN PREMI ASURANSI JIWA BERJANGKA SINGLE LIFE MENGGUNAKAN MODEL COX-INGERSOLL-ROSS (CIR) - Romaito Br Silalahi (Math Program, Math and Science faculty, Pamulang University, 2022)
Premium is an amount of money that must be paid by the customer at a certain time based on an insurance policy. This study aims to determine the value of single life term life insurance premiums using the Cox-Ingresoll-Ross (CIR) interest rate model. There are differences in the value of men's and women's premiums from the calculation of single life term life insurance premiums using the CIR interest rate model. The value of the premium paid by men is more expensive than the value of the premium paid by women. The premium value for men is greater than 1.5 times the premium value for women.Key words: premium, life insurance, CIR model